Profiles of miRNAs in serum in severe acute drug induced liver injury and their prognostic significance. (29th November 2016) - Russo, Mark W.; Steuerwald, Nury; Norton, Harry J.; Anderson, William E.; Foureau, David; Chalasani, Naga; Fontana, Robert J.; Watkins, Paul B.; Serrano, Jose; Bonkovsky, Herbert L.
Abstract: Background & Aims: Drug induced liver injury (DILI) is challenging because of the lack of biomarkers to predict mortality. Our aim was to describe miRNA changes in sera of subjects with acute idiosyncratic DILI and determine if levels of miRNAs were associated with 6 month mortality. Methods: Clinical data and sera were collected from subjects enrolled in the Drug Induced Liver Injury Network prospective study. miRNAs were isolated from serum obtained from 78 subjects within 2 weeks of acute DILI and followed up for 6 months or longer. miRNAs were compared to 40 normal controls and 6 month survivors vs non‐survivors. Results: The mean age of the DILI cohort was 48 years, and 55% were female. Eleven (14.1%) subjects died, 10 within 6 months of DILI onset, 5 (45%) liver related. Lower levels of miRNAs‐122, ‐4463 and ‐4270 were associated with death within 6 months ( P <.05). None of the subjects with miRNA‐122 greater than the median value died within 6 months for a sensitivity of 100% and specificity of 57%. In subjects with a serum albumin <2.8 g/dL and miR‐122<7.89 RFU the sensitivity, specificity, positive and negative predictive values for death within 6 months were 100%, 57%, 38% and 100% respectively. Conclusions: Serum miRNA‐122 combined with albumin accurately identified subjects who died within 6 months of drug induced liver injury. If confirmed prospectively, miRNA‐122 and albumin may be useful in identifying patients at high risk for mortality or liver transplantation.